Quo vadis Common Agricultural Policy of the European Union? = Dokąd zmierzasz wspólna polityko rolna Unii Europejskiej? - Stępień, Sebastian; Czyżewski, Andrzej (Zielona Góra: Faculty of Economics and Management Press)
The agricultural policy of the European Union - Common Agricultural Policy (CAP) - was introduced in the 1960s as the first EU policy. Over the next decades it constituted the largest share in the expenditure of the EU budget. Today, although cohesion policy has replaced it in the first place, it is still being prioritized by the countries of the Community.
Keywords: polityka rolna; rozwój zrównoważony; reformy; Unia Europejska; agricultural policy; sustainable development; reforms; European Union